Dual mobility total hip arthroplasty in patients at risk for dislocation - Mohamed M.M Mahmoud (Wolters Kluwer Medknow Publications, 2020)
Background Total hip arthroplasty (THA) is one of the most successful surgeries in orthopedics. However, postoperative dislocation is one of the major complications. There are some patients with higher risk for dislocations. Dual mobility cup THA (DMC) may decrease the rate of dislocation and enhance functional outcome in those patients. Aim The aim was to retrospectively assess postoperative rate of dislocation and functional outcome in patients with preoperative risk factors for dislocation treated by DMC THA. Patients and methods A total of 26 DMC THAs were done for 25 patients with preoperative risk factors for dislocation. Functional outcome by Harris hip score and dislocation rates have been followed for a period of 12-48 months (mean: 31 months). Results There was 0% rate of dislocation till the last follow-up. There was marked improvement in Harris hip score, with good to excellent results in 74% of patients. Conclusion DMC THA is a good option for patients at risk for dislocations, with very low or no rate of dislocation, with good functional outcomes.